2006
DOI: 10.1080/09658210600646716
|View full text |Cite
|
Sign up to set email alerts
|

What people believe about memory

Abstract: Two representative samples of adult Norwegians (n=2000) were asked a set of general and specific questions regarding their beliefs and opinions about human memory. The results indicate that on many questions, such as time of the earliest memories, inhibiting effects of collaboration, and memory for dramatic versus ordinary events, the views of the general public concurred with current research findings, and people in general had realistic views about their own memory performance. On other questions, such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 82 publications
3
66
1
Order By: Relevance
“…That is, individuals who held more negative opinions about children's general eyewitness abilities rated the child victim as being less credible. This makes intuitive sense and supports the extant literature that suggests people's prior biases about children affect concurrent perceptions and decisions in abuse cases (e.g., Magnussen et al, 2006;Wessel et al, 2013). We extended Wessel et al's findings on prior opinions in a physical abuse case to the current scenario which involved CSA.…”
Section: Prior Opinionssupporting
confidence: 77%
“…That is, individuals who held more negative opinions about children's general eyewitness abilities rated the child victim as being less credible. This makes intuitive sense and supports the extant literature that suggests people's prior biases about children affect concurrent perceptions and decisions in abuse cases (e.g., Magnussen et al, 2006;Wessel et al, 2013). We extended Wessel et al's findings on prior opinions in a physical abuse case to the current scenario which involved CSA.…”
Section: Prior Opinionssupporting
confidence: 77%
“…These views can be at odds [8][9][10][11][12] with what has been revealed by the scientific study of memory and its development. For example, many jurors and legal professionals (e.g., judges, lawyers, police) in North America 8 and Europe (e.g., Sweden 13 and Norway 14 ) are naïve when it comes to understanding how memories are formed, how they become distorted over time, and how stress and emotion affect remembering [15][16] .…”
Section: Introductionmentioning
confidence: 75%
“…However, these narratives were sparse on peripheral information and contained reconstructive errors 5 . In an effort to understand whether 'common sense' views of memory are consistent with what the scientific study of memory has revealed, a number of researchers [8][9][10][11][12][13][14][15][16][17] have posed questions about how memory operates to various legal professionals (lawyers, law enforcement officers, judges) as well as members of the general public who are eligible for jury service. As it turns out, the common sense view of memory is frequently inconsistent with the findings from memory research.…”
Section: Box 1 Adults' Courtroom Evidence Of Alleged Memories Of Chimentioning
confidence: 99%
“…A survey of professionals in Norway showed that psychologists had more realistic views of children as witnesses than had the legal professions (Melinder, Goodman, Eilertsen, & Magnussen, 2004). In the present paper, we report a survey of a large sample (n = 857) of licensed psychologists, members of the Norwegian Psychological Association, combining items from the eyewitness questionnaire (Magnussen et al, 2008(Magnussen et al, , 2010Wise & Safer, 2004) with the memory survey of the general public (Magnussen et al, 2006) and adding an item on an issue that still seems to be disputed (Davis & Loftus, 2009), namely the question of repressed and recovered memories. The items represent memory issues on which psychologists may testify in court and issues they might face in the psychological practice.…”
mentioning
confidence: 99%